Analisis Penerapan Kedisiplinan Pada Siswa Kelas V SD Negeri 2 Klapagading, Banyumas - Nugrahaeni Setyo Utari; Dedy Irawan (CENDEKIAWAN, 2024)
Character is essential in achieving the stage of learning success for students. A person with good character is someone who can make decisions and is ready to take responsibility for all the consequences of the decisions made, as well as being disciplined in character. Disciplinary character is the behavior of someone who is obedient and orderly to various existing rules or regulations. This research aims to explore, examine and instill discipline education, as well as find out violations of its application in elementary school-age children. It is expected to instill the disciplinary character of elementary school children in this modern era. This research uses a qualitative approach by focusing on observation and interview studies. The results of this research case study are an analysis of the application of character in elementary schools and the factors that cause violations of discipline. School regulations are the foundation for the implementation of student character development. Some findings related to the application of discipline and education are: (1) Flag ceremonies every Monday or on other national commemorative days; (2) Respecting the flag, praying, greeting teachers; (3) Greeting teachers who arrive early or leave the classroom; (4) Conducting the Clean Friday activities. By implementing school rules, it is possible to cultivate children's disciplined character, especially in elementary school students